Bridging the Role of Evidence-Based Studies and Policy: A Study on Border Management Policy Formulation in North Central Timor District - Yohanes Fritantus (Wacana Journal of Social and Humanity Studies, 2021)
The research objective was to (1) identify research themes for the development of border areas in the Regional Border Management Agenc of North Central Timor Regency; and (2) to analyze and describe the communication of research and policy formulation at the Regional Border Management Agency of North Central Timor Regency. The research approach used is descriptive qualitative research methods. Qualitative descriptive research was used to obtain communication between research and policy formulation of border management policies at the Regional Border Management Agency of North Central Timor Regency. Determination of sampling using snowball sampling, by collecting information continuously until the information is considered saturated. Collecting-data using’in-depth interview-technique, observation and ddocumentation.The results show that, First: research themes related to border area management are prioritized on several aspects, namely institutional aspects, boundary management aspects, cooperation aspects, and infrastructure aspects.Second: communication of research results in policy formulation is not optimal and is influenced by several obstacles, namely at the Interface A stage where the communication process / communication strategy between researchers and the Regional Border Management Agency of North Central Timor Regency has not been implemented since the stage of determining the research issue. Interface Phase B, that the proactive dissemination process involves the Regional Border Management Agency of the North Central Timor Regency, must be increased even though the published research (research results availability), related to border management in North Central Timor Regency, is sufficient and easy to access. In addition, the institutional aspects related to the human resources of the Regional Border Management Agency for the North Central Timor Regency are still very limited in quantity.